Control of the photocatalytic activity of bimetallic complexes of pyropheophorbide- A by nucleic acids - Arian, Dumitru; Kovbasyuk, Larisa; Mokhir, Andriy (Inorganic Chemistry, 2011)
Photocatalytic activity of a photosensitizer (PS) in an oligodeoxyribonucleotide duplex 5′-PS∼ODN1/ODN2∼Q-3′ is inhibited because of close proximity of a quencher Q. The ODN2 in this duplex is selected to be longer than the ODN1. Therefore, in the presence of a nucleic acid (analyte), which is fully complementary to the ODN2 strand, the duplex is decomposed with formation of an analyte/ODN2∼Q duplex and a catalytically active, single stranded PS∼ODN1. In this way the catalytic activity of the PS can be controlled by the specific nucleic acids. We applied this reaction earlier for the amplified detection of ribonucleic acids in live cells (Arian, D.; Cló, E.; Gothelf, K.; Mokhir, A. Chem.-Eur. J.2010, 16(1), 288). As a photosensitizer (PS) we used In (pyropheophorbide-a)chloride and as a quencher (Q) - Black-Hole-Quencher-3 (BHQ-3). The In complex is a highly active photocatalyst in aqueous solution. However, it can coordinate additional ligands containing thiols (e.g., proteins, peptides, and aminoacids), that modulate properties of the complex itself and of the corresponding bio- molecules. These possible interactions can lead to undesired side effects of nucleic acid controlled photocatalysts (PS∼ODN1/ODN2∼Q) in live cells. In this work we explored the possibility to substitute the In complex for those ones of divalent metal ions, Zn and Pd , which exhibit lower or no tendency to coordinate the fifth ligand. We found that one of the compounds tested (Pd(pyropheophorbide-a) is as potent and as stable photosensitizer as its In analogue, but does not coordinate additional ligands that makes it more suitable for cellular applications. When the Pd complex was introduced in the duplex PS∼ODN1/ODN2∼Q as a PS, its photocatalytic activity could be controlled by nucleic acids as efficiently as that of the corresponding In complex. © 2011 American Chemical Society.